Addressing sexual health among women who use substances in the marginal urban communities of Latin America: an ethnographic analysis and pilot survey - Laura R Glasman; Julia Dickson Gomez; Gloria Bodnar; Wendy Cuellar (Elsevier, 2018)
Background: In marginal urban communities in Latin America, female substance users are at high risk of HIV, sexually transmitted infections (STIs), and unintended pregnancies, which result, in part, from community violence and cultural sanctions against women who use substances. We did formative research and pilot work to develop what may be the first integrated sexual health intervention for Latin American female substance users. We specifically aimed to adapt a multilevel HIV prevention programme for crack users to the circumstances of female substance users in marginal urban communities of San Salvador, El Salvador. We hypothesised that contexts that stigmatise female sex and substance use and condone violence hinder female substance users' service use and make them more dependent on men and vulnerable to sexual coercion. Methods: From Nov 1, 2015, to Dec 31, 2016, we conducted ethnographic observations and mapped organisations that served women in a large marginal community. We also undertook focus groups and a pilot survey to identify female substance users' perceptions of services and experiences of stigma. Finally, we implemented "plan, study, and act" circles to adapt and pilot test peer-counselling sessions with networks of female substance users, which addressed the interpersonal context of female substance users' sexual health with partners and providers. Findings: We did not find any services directed to female substance users, and organisations targeting women were unaware of the problem. In focus groups (n=18), women reported fear of being judged for using drugs, especially when pregnant or caring for children. Women reported avoiding services or hiding their substance use from providers and receiving verbal aggression from health-care staff. In surveys (n=38), 24 (64%) female substance users who would not request HIV testing would accept it from a friend and nearly all felt more comfortable with integrated HIV/STI and pregnancy prevention than with standalone services. Women in the counselling sessions (n=16) reported more equitable gender norms and safer sex motivations, and greater self-efficacy to prevent sexual coercion than women in a control group (n=18). Interpretation: Interventions to address female substance users' sexual health in these communities should (a) raise awareness of gender norms and associated stigmas; (b) train health-care staff to identify female substance use and address female substance users' sexual health; (c) provide peer-referrals of female substance users to integrated services; and (d) empower female substance users' networks to decrease their vulnerability to coercion and to develop skills to communicate with providers. Funding: US National Institute of Mental Health 5P30MH052776-22 and P30MH052776-23.